Prevention of hypothermia in trauma victims ‐ the HYPOTRAUM 2 study. (19th March 2021) - Lapostolle, Frédéric; Garrigue, Bruno; Richard, Olivier; Weisslinger, Lisa; Chollet, Charlotte; Lagadec, Steven; Soulat, Louis; Ricard‐Hibon, Agnès; Hilaire‐Schneider, Christelle; Debaty, Guillaume; Mazur, Valérie; Vicaut, Eric
Abstract: Introduction: Hypothermia is common in trauma patients. It contributes to increasing mortality rate. Hypothermia is multifactorial, favoured by exposure to cold, severity of the patient's state and interventions such as infusion of fluids at room temperature. Aim: To demonstrate that specific management of hypothermia (or of the risk of hypothermia) increases the number of trauma patients arriving at the hospital with a temperature >35°C. Design: This is a prospective, multicentre, open‐label, pragmatic, cluster randomized clinical trial of an expected 1, 200 trauma patients included by 12 out‐of‐hospital mobile intensive care units (MICU). Trauma patients are included in a prehospital setting if they present at least one of the following criteria known to be associated with an increased incidence of hypothermia: ambient temperature <18°C, Glasgow coma scale <15, systolic arterial blood pressure <100 mm Hg or body temperature <35°C. Patients are randomized, by cluster, to receive a conventional management or 'interventional' nursing management associating: continuous epitympanic temperature monitoring, early installation in the heated ambulance (temperature target >30°C controlled by infrared thermometer), protection by a survival blanket, and use of heated solutes (temperature objective >35°C controlled by infrared thermometer). The primary end point is the prevalence of hypothermia on arrival at the hospital. The hypothesis tested is a reduction from 20% to 13% in the prevalence of hypothermia. Secondary end points are to evaluate the interaction between the effectiveness of the measures taken and: (1) the severity of the patients assessed by the Revised Trauma Score; (2) the meteorological conditions when they are managed; (3) the time of care; and (4) therapeutic interventions. Discussion: This trial will assess the effectiveness of an invasive, out‐of‐hospital, temperature management on the onset of hypothermia in moderate to severe trauma patients. Impact: Specific management of hypothermia is expected to decrease hypothermia in trauma patients.